First Principles Study and Experimental Investigation of Graphene-Molybdenum Disulphide Nanocomposites Based Passive Saturable Absorber - Siti Nabilah Mohd Halim; Fauzan Ahmad; Muhammad Quisar Lokman; Husni Hani Jameela Sapingi; Mohamad Fariz Mohamad Taib; Wan Mohd Fazli Wan Nawawi; Hafizal Yahaya; Mohd Azizi Abdul Rahman; Suhaidi Shafie; Sulaiman Wadi Harun (Photonics, 2022)
Research on hybrid graphene with other two-dimensional materials has gained considerable attention owing to their potential applications beyond single components. Through our first principles analysis via density functional theory, graphene-molybdenum disulphide (MoS2) demonstrated a band gap opening by 2 meV, from gapless graphene when MoS2 layer is introduced into the structure. The simulated graphene-MoS2 has a direct band gap situated at K point of Brillouin zone with preserved Dirac properties of graphene. The experimental studies on graphene-MoS2 also have been performed by preparing graphene-MoS2-chitin nanocomposite through facile liquid-phase exfoliation method. Apart from energy gap using Tauc relation, the physical morphology and nonlinear properties of the material were systematically characterized. Graphene-MoS2-chitin exhibits a modulation depth of 10.5%, which is lower than individual graphene but higher than individual MoS2. Further investigation on the material’s performance was done by integrating the fabricated film into Erbium-doped fiber laser. Stable nanosecond pulse laser operation was realized with graphene-MoS2-chitin hybrid saturable absorber. The pulse width was measured to be 156.4 ns with repetition rate of 1.89 MHz, corresponding to a peak power of 56.13 mW and pulse energy of 8.78 nJ.